Daya simpan buah pepaya potong dengan blanching menggunakan asam askorbat dan natrium benzoat - Nur Fattin; Tri Rahayuni; Maherawati Maherawati (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Consumption of fruit and vegetables in Indonesia is still low. One way to increase fruit consumption is the use of sliced fruit in snack boxes. The preparation of sliced fruit in snack boxes has not been carried out because the durability of cut fruit is very short due to the fruit's physiological characteristics, which is still doing respiration and the presence of enzymatic activity that causes browning. The blanching process can do enzymatic reaction inhibition. This study aims to determine the shelf life of sliced pepaya fruit using the hot water blanching method using ascorbic acid and sodium benzoate immersion. This study used a randomized block design with 1 factor, namely the addition of anti-browning agents in the form of 1% ascorbic acid and 1% sodium benzoate. Storage was carried out for seven days, and parameter observations were carried out on days 0, 1, 3, 5, and 7. The parameters observed were moisture content, vitamin C, pH, texture, and sensory tests (color, aroma, texture, taste, and overall preference). The results showed a decrease in moisture content, vitamin C, pH, and texture of sliced pepaya fruit during storage in all treatments. Blanching by immersion using ascorbic acid can increase vitamin C levels and decrease the pH value of sliced pepaya during storage. Immersion with ascorbic acid and Na benzoate not affected on sliced pepaya’s texture during storage. Sensory testing showed that the immersion of ascorbic acid and Na benzoate could maintain the color, aroma, taste, and overall preference of the panelists for sliced pepaya during storage.